WAQI’IYATU AL-MUJTAMA’I AL-ARABI AL-JAHILI FI AL-MUALLAQAT LI ZUHAIR BIN ABI SULMA - Dayyanah, Tahliyatud; Masadi, M. Anwar (Annual International Conferences on Language, Literature, and Media, 2021)
Reading Al-Zuhair bin Abi Salma’s Mu’allaqah was like calling the reader to see the true reality. His work depicts the reality of pre-Islamic Arab society by reflecting on the history that took place at that time. Literary works cannot be separated from the social reality that surrounds them. The author becomes a part of society and writes in his literary work by taking in things and the reality of the society that surrounds him. The aim of this research is to know the images of the pre-Islamic Arab society in the work of Zuhair bin Abi Salma. The research subject is twenty verses of Al-Zuhair's Mu'allaqat.  As a library research, the method of data collection used was reading to interpret the work. The descriptive analysis used the model of Miles and Huberman, covering data collection, data presentation, data reduction and conclusions. The results obtained from the description of Al-Zuhair bin Abi Salma in his Mu’allaqat are: 1) The position of the woman was humiliated in the pre-Islamic era 2) Peace over wars between tribes (the war of Duheish and Ghabra) for a long time 3) Moral values that arise as a result of a specific event at that time.